Mati naša, daj nam danes naš vsakdanji kruh! - Smerdel, Inja (Etnolog. Nova vrsta (Ljubljana), 2002)
The treatise's introduction explains the reasons for and the beginnings of theresearch into (manual) grain mills in north-eastern Slovenia. A survey of the past ethnological and archaeological research into grain mills is followedby a geographic, historical, and cultural presentation of grain mills in Slovenia and the research on them. The central section of the text consistsof excerpts from available sources and field notes referring to mill stones, how they were split, shaped and processed; workshops, tools, and journeymen stonemasons; transport and trade. Together they construct an image of how grain mills were made in the quarries below Donačka gora and in Rifnik. This is followed by an analysis of womenćs stories about the place of grain mills in the daily food preparation cycle and about the care dedicated to bread. The study is concluded by summary findings and reflections on the significance of grain mills - for centuries a symbolic object of autarchy - and about the eternal, global connection of this cultural element with women They substantiate the word association "grain mill-bread-poverty-women".
Keywords: ethnology; etnologija; žito; mlini; žrmlje; kamnoseki; kamnolomi; kruh; woman; ženske; Slovenia; Slovenija